2023
DOI: 10.25100/cm.v54i3.5353
|View full text |Cite
|
Sign up to set email alerts
|

JAK2, CALR, and MPL Mutation Profiles in Colombian patients with BCR-ABL Negative Myeloproliferative Neoplasms

Ana Isabel Giraldo-Rincon,
Sara Naranjo Molina,
Natalia Gomez-Lopera
et al.

Abstract: BackgroundAmong the chronic myeloproliferative neoplasms (MPNs) not associated with BCR-ABL mutations are polycythemia vera, primary myelofibrosis, and essential thrombocythemia. These diseases are caused by gene mutations, such as the JAK2, MPL, and CALR genes, which regulate the JAK-STAT signaling pathway. ObjectiveThis study aimed to establish the frequencies of mutations in the JAK2, MPL, and CALR genes in Colombian patients with a negative clinical diagnosis of BCR-ABL chronic myeloproliferative neoplasms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Although these co-mutations are rare in MPN patients, there have been a few reports ( 54 , 55 ). For instance, patients with CALR and JAK2 gene co-mutations were found in Colombian MPN patients ( 56 ). Min-Gu Kang et al found that JAK2 and CALR mutations coexisted in 7 (4.2%) of 167 ET patients ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these co-mutations are rare in MPN patients, there have been a few reports ( 54 , 55 ). For instance, patients with CALR and JAK2 gene co-mutations were found in Colombian MPN patients ( 56 ). Min-Gu Kang et al found that JAK2 and CALR mutations coexisted in 7 (4.2%) of 167 ET patients ( 57 ).…”
Section: Discussionmentioning
confidence: 99%